A rare complication of acute appendicitis – case presentation - Dan DUMITRESCU; Costel SAVLOVSCHI; Sorin OPRESCU; Dragos SERBAN; Sebastian GRADINARU; Tiberiu TROTEA; Bogdan SOCEA; Catalin ALIUS; Victor DUMITRESCU (Archives of the Balkan Medical Union, 2019)
Introduction. Considered by many authors a vestigial structure, the appendix is a small dimensions organ with mostly unknown functions. Acute appendicitis is the most common condition of the ileocecal appendix, having multifaceted clinical manifestations, often masquerading as various unrelated syndromes, but causing increased morbidity, especially when diagnosed late. Although the disease could manifest at any age, there is a progressive increase of its incidence from birth, with a maximum between 10 to 40 years.